Carbapenem-resistant Gram-negative bacteria exhibiting clinically undetected cefiderocol heteroresistance leads to treatment failure in a murine model of infection - Liu, Hongwei; Zhou, Peng; Ma, Peng; Liu, Yaqin; Zhang, Yingfeng; Li, Qiwei; Xu, Lingqing; Yuan, Wenchang; Yin, Weiguo; Li, Linhai; Lu, Yang (Frontiers in Microbiology, 2025)
IntroductionCarbapenem-resistant (CR) Gram-negative pathogens are classified by the WHO as critical threats due to limited therapeutic options. Cefiderocol (CFD), a novel siderophore cephalosporin, shows promise but remains unapproved in China. This study investigated the prevalence, clinical impact, and genetic mechanisms of cefiderocol heteroresistance (CFD-HR) in CR and ESBL-producing clinical isolates from China, where CFD remains unapproved.MethodsA total of 407 CR and ESBL-producing isolates were analyzed. CFD-HR was identified by population analysis profiles (PAPs). Clinical relevance was assessed through disk diffusion susceptibility testing, time-kill assays, and a murine peritonitis model. Genetic mechanisms and stability were elucidated by whole-genome sequencing (WGS) and fitness cost assays.ResultsCFD-HR prevalence was 17.4% (16/92) in carbapenem-resistant A. baumannii (CRAB), 27.9% (24/86) in carbapenem-resistant P. aeruginosa (CRPA), 23.8% (10/42) in carbapenem-resistant E. coli (CRE), and ≤10% (1/10 in ESBL-producing P. aeruginosa and 8/177 in ESBL-producing E. coli). Although 72.9% (43/59) of HR isolates were classified as CFD-susceptible by disk diffusion, time-kill assays showed that 66.7% (4/6) of HR strains required ≥8 mg/L CFD (vs. 4 mg/L for non-HR) to prevent regrowth. In vivo, CFD achieved 100% (3/3) survival in non-HR infections but only 16.7% (4/6) in HR-infected mice. WGS identified transient genetic alterations in HR subpopulations, including sitABCD duplications (CRE), oprD mutations (CRAB), and vgrG SNPs (CRPA), which reverted after antibiotic withdrawal. Fitness cost assays revealed unstable growth deficits in 33.3% (2/6) of HR subpopulations, correlating with genetic instability.DiscussionThese findings highlight the clinical significance of CFD-HR, even in susceptible isolates, and underscore the need for improved diagnostic methods to detect HR and monitor cross-resistance, offering critical insights for regions transitioning to CFD implementation.